Effect of Laser Fluence on a Microarray Droplets Micro-Organisms Cells by LIFT Technique. (July 2017) - Haider, Adawiya J.; Haider, Mohammed J.; Majed, Mirvat D.; Mohammed, Asma H.; Mansour, Hazim L.
Abstract: Laser Induced Forward Transfer (LIFT) is one important method to fabricate microstructures, and it has been widely used in direct-print many materials with a high degree of spatial re- solution. In present work, The results of the application of the LIFT on micro-organism cells like (Yeast and Escherichia coli ( E.coli ))transfer, a microarray droplets have been created from liquid thin film coated titanium Oxide thin film and study the laser fluence on the droplet transfer with checking the viability of the transferred cells assessing the potential of laser. Titanium Oxide thin films average thickness less than 250 nm, were deposited on glass substrate. For characterization, Scanning Electron Microscope was exercised to check the integrity of micro-organisms cells ( Yeast and E.coli ) which showed maintenance during the process. The MacConkey agriculture media was used to test viability of Yeast and E.coli cells. Further, studying the optimum environments to preserve viability of the transferred yeast cells, these conditions were at laser fluence of 10mJ/cm 2 and 150µm distance between donor and receptor layers.